2D-3D heterostructure enables scalable coating of efficient low-bandgap Sn–Pb mixed perovskite solar cells. (December 2019) - Zeng, Linxiang; Chen, Zongao; Qiu, Shudi; Hu, Jinlong; Li, Chaohui; Liu, Xianhu; Liang, Guangxing; Brabec, Christoph J.; Mai, Yaohua; Guo, Fei
Abstract: Low-bandgap photovoltaic absorbers based on mixed tin-lead (Sn–Pb) halide perovskites offer promising opportunities to fabricate efficient multi-junction solar cells. However, the current Sn–Pb mixed perovskite solar cells (PSCs) were mainly prepared using lab-scale spin-coating, greatly hindering their application for large-area device fabrication. Here, we report a simple and robust methodology for scalable deposition of dense and uniform Sn–Pb mixed perovskite films by one-step blade coating. High quality perovskite films with different Sn–Pb ratios are readily prepared by vacuuming the freshly coated precursor films followed by an anneal process. Solar cells based on these bladed Sn–Pb mixed perovskite absorbers showed decent photovoltaic behaviors. Further enhancement of device performance was realized via surface defects passivation using phenethylammonium bromide (PEABr). It was found that the formation of a thin layer of 2D Ruddlesden-Popper perovskite on top of 3D bulk perovskite significantly suppressed charge recombination. As a consequence, the open-circuit voltage ( V OC ) of the solar cells ( E g = 1.35 eV) was dramatically lifted from 0.71 V to 0.78 V, yielding high efficiencies of over 15%. Moreover, notable improvement in shelf and moisture stability was observed due to the protection barrier of the 2D perovskite capping layer. Graphical abstract: Image 1 Highlights: A simple and robust methodology for scalable deposition of dense and uniform Sn–Pb mixed perovskite films by one-step blade coating is presented. High quality perovskite films with different Sn–Pb ratios are readily prepared by vacuuming the freshly bladed precursor films followed by a low-temperature annealing. Effective surface defects passivation is achieved by coating a solution of phenethylammonium bromide (PEABr) on top of the Sn–Pb perovskites. The formation of the 2D perovskite capping layer enhances the V OC of Sn–Pb perovskite solar cells ( E g = 1.35 eV) from 0.71 V to 0.78 V, yielding high efficiencies of over 15%.